Application of 1D Magnetotelluric Method to Estimate Alluvium Thickness in Aceh River Delta - Fajrul Hani; Nazli Ismail; Muhammad Syukri Surbakti; Fadhli Syamsuddin; Amir Asyqari; Muhammad Nanda; Badrul Munir; Muhammad Arfan Alhafsi; Tomi Afrizal (Department of Physics, Sebelas Maret University, 2026)
The Aceh River Delta, located in Banda Aceh City and Aceh Besar Regency, is a Quaternary alluvial plain composed of unconsolidated young sediments and lies between two northern branches of the Great Sumatran Fault, making it vulnerable to earthquake amplification and liquefaction. Estimating the thickness of alluvium is essential for seismic risk assessment. This study applies the 1D magnetotelluric (MT) method to investigate subsurface resistivity and estimate alluvium thickness. MT data were acquired in Cot Seunong Village using a KMS-820 data logger, LEMI-120 magnetometer, and LEMI-701 electrodes for 14 hours. Processing included time-frequency analysis, notch filtering, and robust transfer function estimation using the EMTF algorithm. Apparent resistivity and phase data were inverted using IPI2WIN to produce a 1D resistivity model. The model reveals seven subsurface layers to 1000 m depth, with the upper six layers (0–420 m) having low to moderate resistivity (13.9–134.9 Ωm), interpreted as alluvium. The deepest layer (914.2 Ωm) likely represents sandstone-conglomerate bedrock. The model correlates well with nearby borehole lithology. These findings confirm the effectiveness of the 1D MT method in estimating alluvium thickness and detecting resistivity contrasts. The estimated alluvium thickness of 420 m increases vulnerability to seismic wave amplification at the ground surface. Further surveys using 2D/3D MT inversion are recommended to provide comprehensive information on vertically and laterally subsurface conditions, thereby enhancing geohazard assessment in the Aceh River Delta.